How the observed create ethical dilemmas for the observers: Experiences from studies conducted in clinical settings in the UK and Australia - Bloomer, Melissa J.; Doman, Maggie; Endacott, Ruth (Nursing & health sciences, 2013)
Observational research has a history of controversy, particularly when the research is conducted in a clinical setting. Existing ethical approval processes focus on protecting participants and the researcher's responsibilities, in particular where vulnerable populations are concerned. In this study, the authors explored the less overt and often understated ethical challenges that can arise when conducting observational research in a clinical setting. Reflecting on two recent studies conducted in different clinical settings, the authors described the challenges of blurring role boundaries, the risk of collecting redundant data, and the impact of reverse power relationships between researchers, clinicians, and managers. From their experiences, the authors suggested that the preparatory work undertaken with clinicians and managers onsite, which typically focuses on how the researchers will maintain the ethical robustness of the research and protect the rights of participants and the vulnerable, should also highlight the sometimes overlooked ethical issues associated with participatory research. This can help ensure that participants and managers understand the scope and limitations of the research, and consider the ways in which the observed can influence the researcher and the findings.